An Enantioselective Total Synthetic Approach to (+)-Heptemerone G and (+)-Guanacastepene A from 2-Furyl Methyl Carbinol - Michalak, Karol; Wicha, Jerzy (Synlett, 2013)
An enantioselective synthesis of the key bicyclic building block for (+)-heptemerone G and (+)-guanacastepene A construction has been accomplished. 2-Furyl methyl carbinol was used as the starting material and (S)-4-hydroxy-2-methylcyclopent-2-en-1-one as the primal optically active intermediate.
Keywords: total synthesis; tandem Michael additions; kinetic resolution; rearrangement; tantalum